Exploring EFL students' perceptions and perspectives among different genders on native English teachers’ feedback - I Ketut Wardana (Journal on English as a Foreign Language, 2023)
Corrective feedback (CF) can encourage students to establish realistic learning objectives. Nevertheless, there has been limited investigation on how EFL learners perceive and view feedback delivered by English native teachers, particularly in relation to gender differences. Hence, this study aimed to correlate student perception with perspectives on native English teachers’ feedback, determine differences in male and female perception and describe the level of student's perspectives on the feedback. Quantitative and qualitative methods, with a correlational research design, were employed. Using a simple random sampling technique, a sample of 30 was selected from 150 students from a Bilingual class of Sekolah Lanjut Umum Bawah (SLUB). Post-class questionnaires and interviews were conducted to gather data, which were then analyzed using Pearson Correlation, t-test, and thematic interview analysis. The findings indicated a significant correlation between students' perception and perspective on native English teachers' feedback. In addition, both genders had positive perceptions, with males displaying a more favorable perspective on teacher feedback than females. It also showed students’ "very positive" perspective on teacher feedback. This study highlights the positive impact of English native teachers' feedback on students' views and recommends EFL teachers to employ CF, considering gender-specific needs.